SOCIO-ECONOMIC INSTITUTIONS FOR DEVELOPMENT OF COOPERATION - Sakovska, Olena; Shpykuliak, Oleksandr; Ushkarenko, Iuliia; Chmut, Anna (Financial and credit activity problems of theory and practice, 2018)
The cooperation concept, which in its content can be regarded as an economic phenomenon, the essence of which is the economic relationships between partners in terms of cooperation in order to achieve the common goal of lower specific costs of resources on the basis of mutual benefit for all participants, has become a powerful component and a promising direction. economic development of many countries of the world. The activity of cooperative enterprises takes place in a certain institutional environment, which is defined as a set of fundamental social, political, legal, and economic rules within the framework of human behavior. It is the institutional approach to the cooperation development that is currently at the center of attention of contemporary researchers and needs a detailed analysis. Therefore, the purpose of the article is to study the main institutional imperatives of the development of cooperative relations of business entities in modern conditions. In the article, based on theoretical-methodical analysis and structurally functional approach, the system-forming socio-economic institutes of cooperation are defined. It is determined that among the socio-economic institutions of co-operation, institutions of cost, efficiency, co-operative ideology occupy a significant place. The institution of expenditures is described in detail, defined types of transaction costs (information search, negotiation, measurement, specification and protection of property rights, opportunistic behavior, politicization) and their characteristics in the context of cooperation. The institute of cooperative ideology and its influence on expenses of cooperative association are investigated. It is proved that the main advantage and motive of cooperation is the desire to obtain an additional (synergetic) effect from the interaction of participants. The synergistic effect may be due to the fact that the combined use of several mutually agreed strategies is more beneficial than the isolated implementation of someone and comes as a result of the self-organization of complex systems. The following main elements of the cooperative system of interaction are defined: enterprise integrator, suppliers of material resources, competitors, intermediaries, consumers, etc. The synergy effect in the cooperative is substantiated.